Smart Thermally Actuating Textiles - TUNÇAY ATALAY, ASLI (WILEY, 2020)
Soft robots have attracted attention for biomedical and consumer devices. However, most of these robots are pneumatically actuated, requiring a tether and thus limiting wearable applications that require multiple controlled actuators. By pairing liquid-vapor phase change actuation with a textile-based laminated manufacturing method, smart thermally actuating textiles (STATs) eliminate the need for a pneumatic tether. STATs are lightweight and unobtrusive for wearable applications and exploit a facile manufacturing approach that supports arbitrary customization of the form factor and easy creation of connected arrays of individual robotic modules. Through integrated sensing and heating elements, STATs demonstrate closed-loop feedback that enables dynamic pressure control in the presence of environmental temperature fluctuations.
Keywords: phase change actuators; robotic textiles; soft actuators; soft devices; soft sensors; ARTIFICIAL MUSCLES; STRAIN; FIBER; SENSOR; DESIGN